Pendugaan Cadangan Karbon Pada Tegakan Pohon di Kawasan Hutan Lindung Irier (HLI) Kampung Sewan, Distrik Sarmi Timur Kabupaten Sarmi, Papua - Sammaria J. Karma; Rosye H.R. Tanjung; Hendra K. Maury (Jurnal Biologi Papua, 2021)
Irier Protection Forest in Sewan Village has an area of 750 ha which is included in the Sarmi Lintas Mamberamo Raya KPHP area. This study aims to determine carbon stock value of the forest vegetation. The method to determine the location of the study using purposive sampling with line transect  method to determine the density of vegetation. Furthermore, the method of calculation of the carbon stocks stored calculated using allometric equations. The results showed that the Irier Village Protected Forest Area has 21 trees belonging to 14 families with a total of 343 trees/ha. The value of biomass is 170.61 tons/ha and value of carbon stocks stored in timber stands is 80.18 tons/ha.  Key words: Carbon stocks; Irier village protected forest; Sewan; vegetation